The Epistemic Vices of Democracies in the Age of Populism - Luigi Bonatti (Center for Economic Studies and ifo Institute (CESifo), 2023)
The subject of this paper is how the epistemic limitations of individuals and their biases in reasoning affect collective decisions and in particular the functioning of democracies. In fact, while the cognitive sciences have largely shown how the imperfections of human rationality shape individual decisions and behaviors, the implications of these imperfections for collective choice and mass behaviors have not yet been studied in such detail. In particular, the link between these imperfections and the emergence of contemporary populisms has not yet been thoroughly explored. This is done in this paper by considering both fundamental dimensions of the political space: the cultural-identitarian and the socio-economic one. As has been noted, reflections on these points induce to revise the picture of democracy as a regime producing collective decisions that come out from the interaction of independent individuals well aware of their values and interests, and rationally (in the sense of rational choice theory) pursuing them. This leads to a certain skepticism towards the idealization of democracy as human rationality in pursuit of the common good, which serves to provide cover for those who profit from the distortions and biases in the policy-making processes of actual democracies. A natural conclusion of the paper is that contemporary democracies are quite vulnerable in the face of populist leaders and parties, that are systematically trying to exploit to their advantage people's imperfect rationality (using "easy arguments", emotions, stereotypes…).
Keywords: P00; Z10; 330; bounded rationality; Plato's political philosophy; cognitive sciences; social psychology; evolutionary psychology; social identity